Strategi Kepala Sekolah Dalam Mengelola Konflik Internal - Sabariah, Sabariah; Ulfah, Annisa; Ikhwan, Ikhwan; Rufi'i, Rufi'i; Gunawan, Wawan; Hamid Bashori, Abdul (Universitas Negeri Surabaya, 2024)
The aim of the research is to explain and describe the strategies used by schools in managing conflict at Banua Jingah 1 State Elementary School. The research method is qualitative through a phenomenological approach. Data collection techniques using interviews, observation and documentation. Data processing by collecting data, dividing data by groups, research ideas and drawing conclusions. The results of the research show: conflict occurs due to misunderstandings in the communication process originating from the school principal and also the school community due to differences of opinion or gaps between school members. Conflict resolution strategies, firstly a collaborative strategy involving all school human resources to work together to resolve the conflict. The second accommodation strategy involves combining various opinions about solving problems that are suitable for school conflicts. The third strategy is to compromise by resolving problems through a middle way (not taking sides) in resolving conflicts at school.